ANALYZING THE STATUS OF WOMEN IN E-GOVERNANCE ERA OF BANGLADESH: CHALLENGES AND POTENTIALS - Zisan, Tasnuva Habib (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
This study examines the present status of women in the context of Electronic governance initiatives in Bangladesh. As a developing country, Bangladesh is stepping toward achieving E-governance where there is always a debate of the digital divide. Hence, this study tries to explore the challenges faced by women for access to and control over resources specifically the Information and Communication Technology tools or devices. It also aims to unveil the potentials of women's access and usage of such resources. This study employs survey data collected from study areas. Both urban and rural areas are chosen to get an overall scenario of women's status. This study is conducted in an inductive approach and findings are analyzed in a qualitative approach. The result shows that the status of women in access and usage of ICT varies in urban and rural areas due to some common constraints. The major findings of the study suggest that Information and Communication Technology has some potential for women empowerment which is explained as a case study. In this era of E-governance, most women are still facing gendered challenges such as lack of control over resources, awareness, education, and cybersecurity.JEL Classification Codes: H41, J70, O33, O38.